2009
DOI: 10.1038/ejhg.2009.134
|View full text |Cite
|
Sign up to set email alerts
|

The common biological basis for common complex diseases: evidence from lipoprotein lipase gene

Abstract: The lipoprotein lipase (LPL) gene encodes a rate-limiting enzyme protein that has a key role in the hydrolysis of triglycerides. Hypertriglyceridemia, one widely prevalent syndrome of LPL deficiency and dysfunction, may be a risk factor in the development of dyslipidemia, type II diabetes (T2D), essential hypertension (EH), coronary heart disease (CHD) and Alzheimer's disease (AD). Findings from earlier studies indicate that LPL may have a role in the pathology of these diseases and therefore is a common or sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 55 publications
1
28
0
2
Order By: Relevance
“…We did not identify any eligible abstracts. We translated one article that was published in Chinese [28]. Agreement on article inclusion after full-text assessment was excellent (kappa 1.0).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not identify any eligible abstracts. We translated one article that was published in Chinese [28]. Agreement on article inclusion after full-text assessment was excellent (kappa 1.0).…”
Section: Resultsmentioning
confidence: 99%
“…In one of these trials, not all patients were admitted to the ICU but due to inclusion of severe pancreatitis patients with a mortality rate of 25% we decided to include it [32]. Nine trials investigated the use of jejunal feeding tubes [10,20,26,28,30-32,35,36] and six the use of duodenal feeding tubes [21,23-25,33,34], whereas the rest did not specify the location of the feeding tube in the small intestine [22,27,29,37]. VAP preventive strategies were not described consistently in the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ãåíû, âîâëå÷åííûå â ðåãóëÿöèþ ëèïèäíîãî îáìåíà (ËÎ), ðàññìàòðèâàþòñÿ êàê çíà÷èìûå ãåíåòè-÷åñêèå ôàêòîðû ðèñêà ÈÁÑ [7,11]. Ñðåäè âîçìîaeíûõ ãåíîâ-êàíäèäàòîâ ïîäâåðaeåííîñòè ÈÁÑ âûäåëÿþò ãåí ëèïîïðîòåèíëèïàçû (LPL ) -ôåðìåíò, îáåñïå÷èâàþ-ùèé ãèäðîëèç òðèãëèöåðèäîâ (ÒÃ) è ïðåâðàùåíèå õî-ëåñòåðèíà ëèïîïðîòåèäîâ î÷åíü íèçêîé ïëîòíîñòè (ÕÑ ËÎÍÏ) â õîëåñòåðèí ëèïîïðîòåèäîâ íèçêîé ïëîò-íîñòè (ÕÑ ËÍÏ) [4,5]. Ïîëèìîðôèçìû ãåíà LPL îïðå-äåëÿþò ôóíêöèîíàëüíóþ àêòèâíîñòü ôåðìåíòà è, òà-êèì îáðàçîì, ìîãóò âíîñèòü âêëàä â ïðåäðàñïîëîaeåí-íîñòü íîñèòåëåé ê ãèïåðëèïèäåìèè (ÃËÏ).…”
Section: ââåäåíèåunclassified
“…A common biological basis for some complex diseases has been reported earlier. 27 By calculating the distribution of the number of genes associated with a disorder, s, we found that most diseases have a few disease genes ( Figure 2a, the average of s was 4.75). However, the top 10 diseases related to cancer, and metabolic, neurological, psychogenic, immune and cardiovascular diseases, have dozens of disease genes.…”
Section: Analysis Of the Topological Featuresmentioning
confidence: 99%